Detection of the biotype and genomic type of bovine viral diarrhea virus (BVDV) from acute/peracute field cases - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Six isolates collected from animals that died of an acute/peracute BVDV infection were used for detecting the bio- and genomic types of new clinical form of BVDV. Using IPMA and PCR techniques the biotype and genotype of BVDV from all those cases were identified as NCP-BVDV type 2.